2023
DOI: 10.1161/hypertensionaha.122.19733
|View full text |Cite
|
Sign up to set email alerts
|

Genomic, Transcriptomic, and Proteomic Depiction of Induced Pluripotent Stem Cells–Derived Smooth Muscle Cells As Emerging Cellular Models for Arterial Diseases

Abstract: BACKGROUND: Vascular smooth muscle cells (SMCs) plasticity is a central mechanism in cardiovascular health and disease. We aimed at providing cellular phenotyping, epigenomic and proteomic depiction of SMCs derived from induced pluripotent stem cells and evaluating their potential as cellular models in the context of complex diseases. METHODS: Human induced pluripotent stem cell lines were differentiated using RepSox (R-SMCs) or PDGF-BB (platelet-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 78 publications
0
11
0
Order By: Relevance
“…The field is advancing with novel strategies to differentiate VSMCs without having to expose cells to different growth factors that may variably influence the phenotype of VSMCs, as highlighted in the current issue. 3 Liu et al 3 implemented a protocol using the small molecule RepSox, identified as a promoter of SM-MHC positive cell differentiation via activation of NOTCH signaling, 8 as a model for development of procontractile VSMCs (R-SMCs). The authors compared this model with the classical TGF-β/PDGF model of VSMC differentiation (TP-SMCs; Figure ).…”
Section: See Related Article Pp 740-753mentioning
confidence: 99%
See 4 more Smart Citations
“…The field is advancing with novel strategies to differentiate VSMCs without having to expose cells to different growth factors that may variably influence the phenotype of VSMCs, as highlighted in the current issue. 3 Liu et al 3 implemented a protocol using the small molecule RepSox, identified as a promoter of SM-MHC positive cell differentiation via activation of NOTCH signaling, 8 as a model for development of procontractile VSMCs (R-SMCs). The authors compared this model with the classical TGF-β/PDGF model of VSMC differentiation (TP-SMCs; Figure ).…”
Section: See Related Article Pp 740-753mentioning
confidence: 99%
“…Taken together, the work from Liu et al 3 has revealed new models to study genetic and epigenetic factors relevant to cardiovascular diseases. In addition to deeply characterizing iPSC-SMCs using different cell differentiation approaches, this study 3 further raises important questions as to why gene profiles of apparent contractile and proliferative VSMCs differ depending on the experimental strategies used to differentiate cells. Moreover, these differential findings raise concerns regarding how closely iPSC-VSMCs recapitulate apparent VSMC changes in vascular changes associated with cardiovascular disease.…”
mentioning
confidence: 97%
See 3 more Smart Citations